Developing Instrument of Essay Test to Measure the Problem-Solving Skill in Physics - Aristiawan, A.; Istiyono, E. (Jurnal Pendidikan Fisika Indonesia, 2020)
This research was developmental research with the final product is test instrument to measure the students’ physics problem-solving skills of the Senior High School. The problem-solving aspects measured contained of understanding the problem, organizing the knowledge, carrying out the plan, and evaluating the solution. This research used a modified Oriondo Dallo-Antonio Development model that comprised of (1) planning test, (2) trying out the test, (3) determining the validity, and (4) determining the reliability. This research was done in the Senior High School in Sleman regency. The result of this research showed that there were two packages of test of which each package consisted of 12 questions included 4 anchor questions. The test was an essay test which the scoring used PCM model based on the five categories of Polytomous data. The item analysis of the test was done first to prove the assumptions that became the basic theory of item response that were one dimensional, local independence, and invariance parameter. The quality of developed test item is good category which the range of mean square score is 0.96 – 1.08 and the difficulty level is -0.7 to 0.41. Based on the information score function and SEM, the developed instrument was good to be implemented for the test participant with the medium ability.